LEARNING MOTIVATION AND THE TEACHER’S ROLE: A CASE STUDY OF STUDENTS WITH INTELLECTUAL DISABILITIES AT SDLB KALIWUNGU KUDUS: KETERKAITAN MOTIVASI BELAJAR DAN PERAN GURU : STUDI KASUS PADA SISWA TUNAGRAHIITA SDLB KALIWUNGU KUDUS - Naela Syahrani; Imaniar Purbasari; Denni Agung Santoso (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
he learning process of students with intellectual disabilities still faces various challenges, including low learning concentration, limited understanding of learning materials, and a tendency to be passive when motivational stimulation is not provided. This study aims to describe the role of teachers in motivating the learning of students with intellectual disabilities at SDLB Kaliwungu Kudus. This research employed a qualitative method with a case study approach. The research subjects included teachers and students with intellectual disabilities at SDLB Kaliwungu Kudus, with data collected through observation, interviews, and documentation. The results of the study indicate that teachers play a very important role in enhancing the learning motivation of students with intellectual disabilities. This role is manifested through their functions as educators, mentors, trainers, and evaluators, which are implemented contextually according to the characteristics and needs of each student. Teachers deliver learning materials in a simple and gradual manner, provide academic and emotional assistance, train habits and basic skills repeatedly, and conduct evaluations that emphasize the learning process and students’ developmental progress.